2021
DOI: 10.1101/2021.03.06.434193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 501Y.V2 (B.1.351) elicits cross-reactive neutralizing antibodies

Abstract: Neutralization escape by SARS-CoV-2 variants, as has been observed in the 501Y.V2 (B.1.351) variant, has impacted the efficacy of first generation COVID-19 vaccines. Here, the antibody response to the 501Y.V2 variant was examined in a cohort of patients hospitalized with COVID-19 in early 2021 - when over 90% of infections in South Africa were attributed to 501Y.V2. Robust binding and neutralizing antibody titers to the 501Y.V2 variant were detected and these binding antibodies showed high levels of cross-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 35 publications
5
31
0
1
Order By: Relevance
“…The plasma neutralizing activity of the 13 healthcare workers infected with B.1.1.7 VOC was found to be highest against the homotypic pseudovirus (i.e., B.1.1.7, GMT: 265) and to be reduced to undetectable levels in most cases against the wildtype (D614G) pseudovirus and the other VOC tested, including B.1.427/B.1.429 (Fig. 2 I,L-M) , which is different from what was observed with B.1.351-elicited Abs ( 35 , 36 ). Since B.1.1.7 is now the prevalent lineage in Europe and several other countries( 26 ) the finding that infection with B.1.1.7 elicits a low level of cross-neutralizing Abs towards the other co-circulating lineages is concerning.…”
Section: Resultsmentioning
confidence: 58%
“…The plasma neutralizing activity of the 13 healthcare workers infected with B.1.1.7 VOC was found to be highest against the homotypic pseudovirus (i.e., B.1.1.7, GMT: 265) and to be reduced to undetectable levels in most cases against the wildtype (D614G) pseudovirus and the other VOC tested, including B.1.427/B.1.429 (Fig. 2 I,L-M) , which is different from what was observed with B.1.351-elicited Abs ( 35 , 36 ). Since B.1.1.7 is now the prevalent lineage in Europe and several other countries( 26 ) the finding that infection with B.1.1.7 elicits a low level of cross-neutralizing Abs towards the other co-circulating lineages is concerning.…”
Section: Resultsmentioning
confidence: 58%
“…Interestingly, the 501Y.V2 (B.1.351) viral variant confers partial to complete resistance to hyper-immune serum and reduces the efficacy of the AZD1222 vaccine [ 92 ] and sera from Pfizer-BioNTech and Moderna subjects displayed considerably decreased effects on 501Y.V2 [ 106 ]. As a consequence, pharmaceutical companies, proposing that changing the immunization sequence would cause a comparable neutralizing effect, trying to counteract the viral variants by replacing the original SARS-CoV-2 immunizing sequence with the 501Y.V2 sequences (i.e., Moderna) [ 107 ]. Therefore, these variants might be especially challenging in patients with cardiovascular diseases based on recent observations on animals [ 108 ].…”
Section: Challengesmentioning
confidence: 99%
“…While animal experiments suggest that adenovirus vaccines still provide sufficient protection of disease after challenge with UK or SA variants [314], a clinical trial in South Africa showed that vaccine efficacy of an approved adenovirus vaccine dropped from >70% to ~10% in preventing mild or moderate disease [336]. Preliminary data indicate that natural infection with the SA variant induces a cross-neutralizing Ab response including potent neutralization of SA mutant viruses, indicating that targeted booster vaccines might be broadly effective [337,338].…”
Section: Sars-cov-2 Mutates On a Low But Constant Level Yielding Mutant Variants Over Timementioning
confidence: 99%